2017
DOI: 10.1080/10888705.2017.1283990
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Bile Extraction From Living Bears: Survey of Citizens and Students in Beijing

Abstract: Bear bile is a traditional Chinese medicine that has been used for millennia. Several arguments support and oppose the use of bear farming in terms of conservation and nonhuman animal welfare. This study involved designing a questionnaire and surveying a random sample of general citizens and college students in Beijing to elicit their attitudes on bile extraction from living bears. Older people and people with lower education levels used more bear bile medicines. In total, 29.47% (n = 204) of citizens and 23.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…The UCT's indirect questions have high statistical error, and our target sample size of 4,000 total surveys would yield a statistical power of >0.8 if consumption prevalence was at least 8%, with individual provincial samples reaching this power if prevalence was 16% (Ulrich et al, 2012). These values are below the only available consumption prevalence estimate for China (23%-30%: Liu et al, 2017), and recent estimates in Vietnam (18%-45%: , suggesting our sample size was adequate. Data collection continued until the target sample size in each district was reached.…”
Section: Public Surveymentioning
confidence: 90%
See 2 more Smart Citations
“…The UCT's indirect questions have high statistical error, and our target sample size of 4,000 total surveys would yield a statistical power of >0.8 if consumption prevalence was at least 8%, with individual provincial samples reaching this power if prevalence was 16% (Ulrich et al, 2012). These values are below the only available consumption prevalence estimate for China (23%-30%: Liu et al, 2017), and recent estimates in Vietnam (18%-45%: , suggesting our sample size was adequate. Data collection continued until the target sample size in each district was reached.…”
Section: Public Surveymentioning
confidence: 90%
“…Younger people reported to consume more wildlife in Southern China (Zhang et al, 2008). Older people reported to use more bear bile products in Beijing (Liu et al, 2017) Gender All people who reported that their last visit to a TCM practitioner was in the last week, month, 6 months or year were combined Consumption of animal-based TCM medicine for serious disease is likely to be mediated by medical practitioners (Liu et al, 2016) Know somebody who uses bile (consumed models only)…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asiatic black bear bile has a medicinal basis, with a long history of use in China for hot ailments such as fever, general pain, inflammation, and epilepsy [14]. Currently, bear bile continues to be used for medicinal purposes in China, with one recent study estimating the prevalence of use at nearly 30% of the Beijing sample [27]. In Vietnam, which shares medical similarities with China, bear bile appears to be used more often and is generally prescribed for much the same ailments, with the most common being bruising, general pain, and fever [28]; however, bear bile as a postpartum treatment was rarely be cited by Vietnamese respondents.…”
Section: Introductionmentioning
confidence: 99%
“…Though bear farming was introduced to meet the demand, the current number has dropped since the Chinese government began to regulate the process, prohibit the hunting of wild bears, stop giving licenses to new farms, and shut off rogue farms that cannot follow the regulation. In addition, the extraction of bile from living bears is considered to be extremely cruel, inhumanly and unethically method, and therefore becoming serious attention from the animal welfare of view (Li et al, 2016;Liu et al, 2017). As a substitution, UDCA is currently made through chemical synthesis by using cholic acid (CA) or chenodeoxycholic acid (CDCA) as starting materials (Figure 1).…”
Section: Introductionmentioning
confidence: 99%